Recent advances in delivery of veterinary DNA vaccines against avian pathogens - Jazayeri, S. D. *; Poh, Chit Laa * (BMC, 2019)
Veterinary vaccines need to have desired characteristics, such as being effective, inexpensive, easy to administer, suitable for mass vaccination and stable under field conditions. DNA vaccines have been proposed as potential solutions for poultry diseases since they are subunit vaccines with no risk of infection or reversion to virulence. DNA vaccines can be utilized for simultaneous immunizations against multiple pathogens and are relatively easy to design and inexpensive to manufacture and store. Administration of DNA vaccines has been shown to stimulate immune responses and provide protection from challenges in different animal models. Although DNA vaccines offer advantages, setbacks including the inability to induce strong immunity, and the fact that they are not currently applicable for mass vaccination impede the use of DNA vaccines in the poultry industry. The use of either biological or physical carriers has been proposed as a solution to overcome the current delivery limitations of DNA vaccines for veterinary applications. This review presents an overview of the recent development of carriers for delivery of veterinary DNA vaccines against avian pathogens.